Effective Heterogeneous Fenton‐Like degradation of Malachite Green Dye Using the Core‐Shell Fe3O4@SiO2 Nano‐Catalyst - Nafis Mahmud (14150004) (2023)
In this study, the application of the core-shell Fe3O4@SiO2 nano-catalysts for fenton-like degradation of malachite green dye has been presented. The nano-catalysts were prepared using a combination of solvothermal and sol-gel techniques and characterized using XRD, FTIR, SEM/EDX, TEM and VSM techniques. The effects of various reaction parameters on the degradation of malachite green dye using the prepared nano-catalysts were investigated. The optimal condition for pH, catalyst dosage and H2O2 amount were found to be at 6.7, 15 mg and 50 μL, respectively. Under the optimized conditions, a degradation efficiency of 96.18 % for malachite green dye was achieved using the catalyst within 30 minutes at 303 K with a pseudo first order rate constant of 0.1102 min−1. The plausible mechanism for MG degradation was determined to be the combination of adsorption and simultaneous decomposition via formation of hydroxyl radicals. The performance of the nano-catalyst was compared with other fenton-like catalysts reported in the literature. Finally, the magnetic properties of the Fe3O4@SiO2 catalysts was utilized for its successful recovery and application in multiple degradation cycles. Other Information Published in: ChemistrySelect License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/slct.202003937